2020
DOI: 10.1093/nargab/lqaa073
|View full text |Cite
|
Sign up to set email alerts
|

Covering all your bases: incorporating intron signal from RNA-seq data

Abstract: RNA-seq datasets can contain millions of intron reads per library that are typically removed from downstream analysis. Only reads overlapping annotated exons are considered to be informative since mature mRNA is assumed to be the major component sequenced, especially for poly(A) RNA libraries. In this study, we show that intron reads are informative, and through exploratory data analysis of read coverage that intron signal is representative of both pre-mRNAs and intron retention. We demonstrate how intron read… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Since D10 is present in the nuclear fraction, we investigated whether pre-mRNAs might be targeted by D10 before intron removal as a mechanism to distinguish transcripts derived from intron-containing and intronless genes. Reads mapping to introns are an accurate readout of pre-mRNA levels [ 29 ]. While exonic reads were reduced upon WT D10 expression, intronic reads were unchanged ( Fig 3E ), suggesting that D10 does not target pre-mRNAs in the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…Since D10 is present in the nuclear fraction, we investigated whether pre-mRNAs might be targeted by D10 before intron removal as a mechanism to distinguish transcripts derived from intron-containing and intronless genes. Reads mapping to introns are an accurate readout of pre-mRNA levels [ 29 ]. While exonic reads were reduced upon WT D10 expression, intronic reads were unchanged ( Fig 3E ), suggesting that D10 does not target pre-mRNAs in the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…Our study revealed many variants in intronic regions. Indeed, it has been shown that the percentage of introns reads was higher when libraries were prepared with total RNA extraction methods, as in the present study, compared with the poly(A) RNA ones [ 40 ]. It should also be noted that the results presented here for variants position do not necessarily reflect the percentages of intron/exon, since variant effect prediction had not been made for all variants but only for those which differ between resistant and susceptible animals.…”
Section: Discussionmentioning
confidence: 73%
“…Specifically, calling RNA editing sites from snRNA-seq is challenging as the technique is limited from extremely low capture efficiency and low sequencing depth with reads covering only a fraction of the entire genome 36,37 . Moreover, intronic regions, which were highly edited in FANS-derived data, often represent high vulnerability to low-coverage in scRNA-seq experiments, where detection of A-to-I events is reduced 38 . Validation rates by snRNA-seq were highest for GLU and MGE-GABA populations, which constituted pools with the largest number of nuclei, and concordance of editing levels for these sites was exceptionally high between snRNA-seq and FANS-derived data sets.…”
Section: Discussionmentioning
confidence: 99%